Increasing Financial Literacy in Empowering Women Bead Craftsmen in Jodipan Colorful Village - Ika Fitria Nur Hamida; Lely Dista Safitri; Maya Ratnasari; Hanif Rani Iswari (TGO Journal of Community Development, 2024)
Jodipan Colorful Village is one of the popular tourist destinations in Malang City, East Java. Behind its beauty, there is a community of women bead craftsmen who are still struggling to improve their economic welfare. Lack of financial literacy is one of the factors inhibiting the village's progress. This community service aims to increase financial literacy and empower women bead craftsmen in Jodipan Colorful Village. Activities carried out include socialization regarding basic financial concepts, financial management, and marketing strategies for bead products. The activity evaluation method is carried out through pre-test and post-test at each session. Apart from that, in-depth interviews and thematic analysis were also carried out with activity participants. To triangulate the data, in-depth interviews were also conducted with KWJ administrators. The results of the service show that the financial literacy of women bead craftsmen in the Jodipan Colorful Village has increased. This is evidenced by their increased knowledge of basic financial concepts, financial management and marketing strategies for bead products.